The Effectiveness of Whispering Games to Teach Speaking - Al Muammamah, Nurfadhilah; Zuhriyah, Mukminatus (IKIP PGRI Pontianak, 2024)
Speaking is one of the language skills related to the role of English as a foreign language in Indonesia. But often uninteresting speaking learning media makes students’ speaking ability low. Therefore, this research was aimed at knowing the effectiveness of Whispering Games to teach speaking at class XI IPA 1 one of private Islamic senior high school in Jombang in the academic year 2023/2024. Nineteen students became the sample of this research. The researchers used a pre-experimental design and a one-group pre-test post-test research design, to analyze the effectiveness of Whispering Game on students’ speaking ability. The result showed that Whispering Game is effective to teach speaking. The result showed that the student's average score was increased from 72.38 to 88.57. The result of a paired-sample T-test with a significant (2-tailed) value of 0.000 indicates that the use of Whispering Game was effective in teaching speaking. Hopefully, the results of this research can be shared as information and knowledge and can be used as a reference for further research.